Diagnostic accuracy of ultrasonography verified with computed tomography for the diagnosis of maxillofacial fractures - A prospective study - Abhishek Shailesh Shah; Tejraj Kale; Virupaxi Hattiholi; Husain Dhabaria (Wolters Kluwer Medknow Publications, 2022)
Objectives: The objective of this study was to evaluate the diagnostic accuracy of ultrasonography (USG) if it can be used as a primary diagnostic method for maxillofacial trauma and to determine the sensitivity and specificity of USG verified with a computed tomography (CT) scan. Materials and Methods: This study was a comparative prospective study that consisted of a total of 32 patients. Patients reported to the Trauma Care and Emergency Center of KLES Dr. Prabhakar Kore Hospital with maxillofacial trauma during October 2018-September 2020 were included in the study. Following a CT scan, based on the inclusion criterion, the patient underwent an ultrasonographic examination of any maxillofacial fracture that had been confirmed by a CT scan to verify it. Sensitivity and specificity were calculated to establish the accuracy of USG. Results: A total of14 sites were selected in the maxillofacial region. Out of all the 14 anatomical landmarks, nine were able to detect all the fractures on USG with 100% sensitivity and specificity. Intracapsular condyle fractures were not seen on USG. The region where all the fractures were not identified on USG was medial wall and floor of the orbit, one nondisplaced ramus fracture. Conclusions: The overall sensitivity observed for the diagnosis of maxillofacial fracture was 85.21% and specificity observed was 100%. In conclusion, USG can be a handy, diagnostic, additional, noninvasive, and inexpensive tool in the detection of maxillofacial fractures when compared to CT in the primary health-care center. Furthermore, studies should be conducted with a considerable amount of sample size as the literature mentions limited work regarding USG as a primary technique in maxillofacial fractures detection.